Healthy Healthy Living Behavior Training as an Effort of Type 2 Diabetes Mellitus Problems: Healthy Living Behavior Training as an Effort of Type 2 Diabetes Mellitus Problems - Michael Vallery Loueis Tumbol; Kevin Pascoal; Indra Lalangpuling (Sam Ratulangi University, 2024)
In North Sulawesi, the prevalence of diabetes mellitus based on a doctor's diagnosis at the age of 15 years is 2.3%, this is higher than the national figure of only 2%, while the prevalence of diabetes mellitus based on a doctor's diagnosis at the age of 15 years in the Minahasa district is 2.29 %. This figure shows that only around 25% of diabetes sufferers are aware that they have diabetes. (Riskesdas, 2018). Kalasey Dua is a village in Mandolang District, Minahasa Regency. The aim of this community service is to improve and apply knowledge and skills to the community as well as form/develop independent community groups in healthy lifestyle patterns in controlling blood sugar. Community service activities for type 2 DM sufferers include counseling and health checks (blood pressure, cholesterol, blood sugar, weight/height), forming partner community groups and monitoring health status for the next three months. The results of this activity, which were evaluated for three months, were that the community had been able to implement healthy living behavior in controlling blood sugar, which included the habit of consuming vegetables and fruit and limiting the consumption of fried foods and meat, doing exercise, reducing smoking and alcohol, regularly taking medication and monitoring blood sugar, and avoid stress. The results of blood sugar, cholesterol, blood pressure and body mass index examinations showed improvements towards normal values. ABSTRAK Di Sulawesi Utara, prevalensi diabetes melitus berdasarkan diagnosis dokter pada umur 15 tahun sebesar 2,3%, angka ini lebih tinggi dari angka nasional yang hanya 2%, sedangkan prevalensi diabetes melitus berdasarkan diagnosis dokter pada umur 15 tahun di daerah kabupaten Minahasa sebesar 2,29%. Angka ini menunjukkan bahwa baru sekitar 25% penderita diabetes yang sadar dirinya menderita diabetes. (Riskesdas, 2018). Kalasey Dua merupakan salah satu desa yang berada di Kecamatan Mandolang, Kabupaten Minahasa. Tujuan pengabdian masyarakat (pengabmas) ini adalah untuk meningkatkan dan menerapkan ilmu pengetahuan dan keterampilan kepada masyarakat serta membentuk/mengembangkan kelompok masyarakat yang mandiri dalam pola perilaku hidup sehat dalam mengendalikan gula darah. Jenis kegiatan pengabmas penderita DM tipe 2 adalah penyuluhan dan pemeriksaan kesehatan (tekanan darah, kolesterol, gula darah, berat/tinggi badan) pembentukan kelompok masyarakat mitra dan pemantauan status kesehatan selama tiga bulan ke depan. Hasil dari kegiatan ini adalah masyarakat telah mampu menerapkan perilaku hidup sehat dalam mengendalikan gula darah yang meliputi kebiasaan mengkonsumsi sayuran dan buah-buahan dan membatasi konsumsi gorengan dan daging, melakukan olahraga, mengurangi rokok dan miras, rutin minum obat dan memantau gula darah, serta menghindari stress. Hasil pemeriksaan gula darah, kolesterol, tekanan darah, indeks massa tubuh menunjukkan perbaikan ke arah nilai normal.